2011
DOI: 10.1115/1.4004076
|View full text |Cite
|
Sign up to set email alerts
|

Robust Thermal Performance of a Flat-Plate Oscillating Heat Pipe During High-Gravity Loading

Abstract: The thermal performance of a miniature, three-dimensional flat-plate oscillating heat pipe (3D FP-OHP) was experimentally investigated during high-gravity loading with nonfavorable evaporator positioning. The heat pipe had dimensions of 3.0 × 3.0 × 0.254 cm3 and utilized a novel design concept incorporating a two-layer channel arrangement. The device was charged with acetone and tested at a heat input of 95 W within a spin-table centrifuge. It was found that the heat pipe operated and performed near-independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…As the heat flux increases, the penetration depth of the FP-OHP's heat affected zone (HAZ) increases [36]; therefore, having greater than two channel layers allows for more working fluid to be vaporized, thus increasing overall heat transfer capability. It has already been found that increasing the number of channel layers from one to two increases the FP-OHP's gravity independence and maximum power limit [19,21,30].…”
Section: Page 9 Of 49mentioning
confidence: 98%
See 2 more Smart Citations
“…As the heat flux increases, the penetration depth of the FP-OHP's heat affected zone (HAZ) increases [36]; therefore, having greater than two channel layers allows for more working fluid to be vaporized, thus increasing overall heat transfer capability. It has already been found that increasing the number of channel layers from one to two increases the FP-OHP's gravity independence and maximum power limit [19,21,30].…”
Section: Page 9 Of 49mentioning
confidence: 98%
“…However, there are still many challenges in engineering optimal two-phase heat spreaders for high heat flux thermal management [27], including (i) establishing a high thermal conductivity in extreme environments (ii) matching material CTEs at the heat source/spreader junction (iii) and minimizing heat spreader thickness (i.e sub-millimeter). Since simulation and/or modeling of heat transfer and fluid dynamics within TGPs is a challenge in its own right [28] [29], compact form factors [30], channel surface modifications [31,32], utilization of nanofluids [33] and increasing the number of channel layers with respect to FP-OHP thickness [21,25,34]. These modifications to the FP-OHP design can result in heat transfer enhancement, higher degree of gravity independence and further miniaturization.…”
Section: Design and Manufacturing Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oscillating heat pipes (OHP), first developed by Akachi [6], have shown significant promise in handling high overall power loads with high heat fluxes [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Unless otherwise noted, the peak power levels described in the following literature review were limited by the test apparatus and chosen heater design.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al(2007) studied that the best performance was obtained when inclination angle of heat pipe was 60°. Thompson et al (2011) investigated the miniature three dimensional FP-OHP. The results indicated that while the inclination angle was 90°, the FP-OHP could dissipate heat flux up to 20 W/cm 2 and kept temperature of heat source below 100°C.…”
Section: Inclination Anglementioning
confidence: 99%